How professional actions connect and protect. Issue 2 (3rd August 2021) - Faulconbridge, James; Folke Henriksen, Lasse; Seabrooke, Leonard
Abstract: Below we provide responses to the ongoing debate sparked by Mirko Noordegraaf's intervention in suggesting that we are moving toward forms of 'connective professionalism'. Critics in this debate have objected to Noordegraaf in a number of ways. Some object to a conflation of ideal types and empirical description. Others assert that Noordegraaf suggests a staged process of moving from protective to connective types of professionalism does not ring true; that we can finds forms of connection and protection in contemporary professionalism and in professional action. Our companions in this issue (Alvehus, Avnoon, and Oliver) suggest that greater connectiveness also permits new forms of protection as part of professionalism. Our short essays contribute to the Noordegraaf debate by focusing less on professionalism and more on how forms of professional action lead to mechanisms of connection and protection.